Differential kinematic features of the hyoid bone during swallowing in patients with Parkinson's disease. (August 2019) - Lee, Woo Hyung; Lim, Min Hyuk; Nam, Hyung Seok; Kim, Yoon Jae; Seo, Han Gil; Bang, Moon Suk; Seong, Min Yong; Oh, Byung-Mo; Kim, Sungwan
Abstract: This study aimed to investigate spatiotemporal characteristics of the hyoid bone during swallowing in patients with Parkinson's disease (PD) and dysphagia. Spatiotemporal data of the hyoid bone was obtained from videofluoroscopic images of 69 subjects (23 patients with PD, 23 age- and sex-matched healthy elderly controls, and 23 healthy young controls). Normalized profiles of displacement/velocity were analyzed during different periods (percentile) of swallowing using functional regression analysis, and the maximal values were compared between the groups. Maximal horizontal displacement and velocity were significantly decreased during the initial backward ( P  = 0.006 and P  < 0.001, respectively) and forward ( P  = 0.008 and P  < 0.001, respectively) motions in PD patients compared to elderly controls. Maximal vertical velocity was significantly lower in PD patients than in elderly controls ( P =  0.001). No significant difference was observed in maximal displacement and velocity in both horizontal and vertical planes between the healthy elderly and young controls, although horizontal displacement was significantly decreased during the forward motion (51st–57th percentiles) in the elderly controls. In conclusion, reduced horizontal displacement and velocity of the hyoid bone during the forward motion would be due to combined effects of disease and aging, whereas those over the initial backward motion may be considered specific to patients with PD.